ENHANCING EMPLOYEE HEALTH THROUGH THE SEBUSE PROGRAM: AN EVALUATION AT PERTAMINA REFINERY UNIT III PLAJU - Rafiqy, Muhammad; Novrikasari, Novrikasari; Misnaniarti, Misnaniarti; Mutahar, Rini; Zulkarnain, Mohammad; Febry, Fatmalina (International Journal of Health Science & Medical Research, 2025)
Since 2021, Pertamina has implemented the SeBuSe (Healthy, Fit, and Happy) program as a corporate health and wellness initiative that operationalizes Health, Safety, Security, and Environment (HSSE) standards. The novelty of this study lies in its strategic integration of the HSSE perspective in evaluating an employee wellness program, its comprehensive application of the SWOT framework for organizational analysis, and its inclusion of participant spouses to capture broader behavioral and motivational dynamics. The program emphasizes holistic well-being through structured activities such as Fat Loss and Move More, designed to support sustained lifestyle improvements. Based on these considerations, this study aims to identify and analyze internal and external factors influencing SeBuSe's effectiveness in improving employee health outcomes using the SWOT analytical approach. Data were collected through Focus Group Discussions (FGDs) involving 30 participants and complemented by in-depth interviews with two program managers and four participant spouses to ensure a multi-perspective understanding of program implementation. The SWOT analysis positions SeBuSe in Quadrant I (Aggressive/Growth Strategy), supported by an internal factor score of 3.10 and an external factor score of 3.46, indicating strong institutional capacity and significant opportunities for further development. Overall, the findings generate strategic insights that can strengthen health promotion efforts and reinforce a proactive safety and wellness culture within Pertamina’s industrial environment.Keywords: Health; Improvement; Productivity; Strategy; SeBuSe; Work.